Single-Port Thoracoscopic Sympathicotomy Using a Double-Lumen Electrocautery Tube and Cautery Hook for Primary Palmar Hyperhidrosis: A Randomized Controlled Trial - Jin, Cheng-Hua; Liu, Kai; Yu, Kai-Zhong; Tian, Hui; Mao, Zheng-Chun; Shen, Wei-Yu (The Thoracic and Cardiovascular Surgeon, 2014)
Objective The objective of this study is to assess the use of a novel, double-lumen electrocautery tube (DLET) device for ablating the sympathetic nerve chain in patients with primary palmar hyperhidrosis (PPH).Methods Forty-six patients with severe PPH were recruited into the study between November 2010 and February 2012. All patients underwent single port, bilateral video-assisted thoracoscopic sympathicotomy. Twenty-four patients were randomized to receive sympathicotomy using a conventional 5-mm electrocautery hook (hook group) and 22 patients were randomized to the DLET group.Results The mean postoperative follow-up period was 8.1 months (range: 1 to 15 months). After surgery the hands of all patients became dry and warm. Mean incision size was 10.6 ± 1.0 in the hook group and 6.5 ± 0.5 mm in the DLET group (p = 0.001). The mean pain score was 1.4 ± 0.6 with hook surgery and 0.9 ± 0.6 with the DLET device (p = 0.016). The mean operative time was longer in the hook group (36.8 ± 3.4 min) than in the DLET group (30.5 ± 3.9 min; p = 0.001). There were no significant differences between the two procedures in terms of hospital stay and compensatory sweating, or patient satisfaction. Pneumothorax occurred in two (8.3%) patients in the hook group and in one (4.5%) patient in the DLET group. None of the patients required chest drainage and none developed Horner syndrome.Conclusions Single-port video-assisted thoracoscopic sympathicotomy using hook or DLET procedures is effective, safe, and minimally invasive method for palmar hyperhidrosis. The DLET device allows a shorter operation time, smaller incision, better cosmetic results, less pain, and better clarity of video, making it suitable for single-port thoracoscopic sympathicotomy.
Keywords: hyperhidrosis; video-assisted thoracoscopic sympathectomy; sympathicotomy